Prediction of arguments and adjuncts in aphasia: Effects of event-related and verb-specific knowledge​ - Rebecca A Hayes; Michael Walsh Dickey; Michael Walsh Dickey (Frontiers in Psychology, 2015)
Previous research suggests that on-line access to lexically-stored verb argument structures is relatively preserved in some people with aphasia[9] (PWAs), despite their increased difficulty in producing verbs as compared to nouns[2]. Accessing lexically-stored argument structures facilitates prediction and integration of verbal arguments relative to lexically unspecified adjuncts[1,8,10]. The anticipatory processing of verbal arguments has also been shown to be affected by event-related plausibility constraints, based in world knowledge[4]. While access to world knowledge and argument structure is preserved in many PWAs, how and when these resources interact during verb-argument processing among PWA has not been investigated.